2017
DOI: 10.18203/2349-2902.isj20172408
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life assessment in stoma patients in a tertiary care hospital in South India: a cross- sectional study

Abstract: Background: Quality of life (QOL) of patients is affected due to procedures done to treat the disease. A good QOL is essential to achieve a holistic approach in treating patients.Methods: We did a cross-sectional study in a tertiary care hospital to describe, identify and compare the factors affecting the QOL of these patients.Results: 42.5% had a permanent stoma and a majority 32.5% were due to a malignancy. Major concerns were skin rash and irritation, depression, loneliness and suicidal thoughts. 62.5% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 7 publications
4
13
0
Order By: Relevance
“…The ratio of colostomy to ileostomy was high (3.25:1), a finding that is in agreement with those of several other studies from a wide range of settings 29,30,32,33 . In the case of our setting, such a ratio is likely because large bowel disease is more prevalent than small bowel disease, as indicated by the initial diagnoses of the participants (Table 1).…”
Section: Participant Characteristicssupporting
confidence: 92%
See 1 more Smart Citation
“…The ratio of colostomy to ileostomy was high (3.25:1), a finding that is in agreement with those of several other studies from a wide range of settings 29,30,32,33 . In the case of our setting, such a ratio is likely because large bowel disease is more prevalent than small bowel disease, as indicated by the initial diagnoses of the participants (Table 1).…”
Section: Participant Characteristicssupporting
confidence: 92%
“…The participants had a mean age of 44.04 +18.47 years that is truly representative of the generally young Ugandan population (WHO, 2016). Relatively younger populations were reported in India 32 and Egypt 30 .…”
Section: Discussionmentioning
confidence: 91%
“…Their desires and values are often not fulfilled nor respected; they feel rejected, seeking seclusion because of the odor and elimination of feces through the abdomen. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…A study on QOL in Muslim ostomate patients demonstrated that standards of QOL in the Muslim population may be improved by proper education and management by stoma care nurses and physician's counselling . At the same time, some researchers proposed that it would be very practical to improve public health policies for stoma patients and for patients to be guided by nursing interventions during the pre‐operating period regarding: possible complications and impacts on body image, clothing, food, sexuality, interpersonal relationships, activities of daily living, and preparation for stoma self‐care, but other studies recommended that stomate patients may benefit from support groups in hospitals . In a systematic review about the effect of education on patients with stoma, the authors concluded that there is a need to test this effect in more controlled studies …”
Section: Introductionmentioning
confidence: 99%